2015
DOI: 10.1590/0001-3765201520140195
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical changes during the loss of desiccation tolerance in germinating Adenanthera pavonina L. seeds

Abstract: We investigated the loss of desiccation tolerance (DT) in Adenanthera pavonina seeds during germination. Seeds were subjected to imbibition for 0, 24, 36, 48, 60 and 81 h, then dried to their initial moisture content (13%), rehydrated and evaluated for survival (resumption of growth and development of normal seedlings) and membrane system integrity (electrolyte leakage). Embryonic axes of seeds subjected only to imbibition during the same early time periods were used to investigate the electrophoretic patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The importance of seed plants to humans is unquestionable and they have been studied for a wide range of aspects (Azevedo et al 1997, Carvalho et al 2011, Bevilaqua et al 2015, Dresch et al 2015, Sneideris et al 2015, Soares et al 2015, but in particular to their nutritional quality due to their consumption by animals and humans (Azevedo et al 1997). Cereals and legume seeds are significant plant protein sources in the human diet (Azevedo et al 1990).…”
mentioning
confidence: 99%
“…The importance of seed plants to humans is unquestionable and they have been studied for a wide range of aspects (Azevedo et al 1997, Carvalho et al 2011, Bevilaqua et al 2015, Dresch et al 2015, Sneideris et al 2015, Soares et al 2015, but in particular to their nutritional quality due to their consumption by animals and humans (Azevedo et al 1997). Cereals and legume seeds are significant plant protein sources in the human diet (Azevedo et al 1990).…”
mentioning
confidence: 99%
“…According to a series of authors, the desiccation tolerance is acquired due the activation of some proteins that accumulate in the final of maturation stages, such as the LEA proteins, which have the capacity to protect important macromolecules for the germination process, such as enzymes and lipids, according to evolution of the dehydration process, conferring to the seeds a greater cellular stability when they enter on the state of vitreous yet (Dalahaie et al, 2013;Kleinwächter et al, 2014;Righetti et al, 2015;Soares et al, 2015). At the drying temperature of 50 °C, it was observed that the capacity of the seeds to withstand desiccation only was attained after the physiological maturity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in the germination and vigor of the seeds of P. aquatica shows that the reduction of the water content negatively affects the physiological quality of the seeds, allowing to classify the seeds of this species as recalcitrant. The water loss in recalcitrant seeds triggers some deteriorating processes, such as protein denaturation, changes in the activity of peroxidase enzymes and damage to the membrane system, resulting in the complete loss of viability (Soares et al, 2015). Unbalanced metabolism and damage due to dehydration are the main causes of loss of viability of seeds during drying (Berjak & Pammennter, 2003).…”
Section: Discussionmentioning
confidence: 99%